2015
DOI: 10.1080/15298868.2015.1022594
|View full text |Cite
|
Sign up to set email alerts
|

(In)Competence Is Everywhere: Self-Doubt and the Accessibility of Competence

Abstract: This research investigated the hypothesis that intellectual competence is chronically accessible to individuals who question their own intellectual competence, despite their own uncertainty on this dimension, and that they rely on intellectual competence in forming impressions of and thinking about others. In two studies, we show that doubtful individuals are more likely to use traits related to intellectual competence to describe others and these traits more strongly affect their overall impressions of others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…1,7,25 Regardless of the discipline, few researchers have used and measured the concept of self-doubt. Hardy et al 12 examined the relationship between self-doubt and individuals' intellectual abilities, which provided information on the phenomenon of self-doubt from a personal intellectual competence perspective. Balkis and Duru 13 examined the relationship between self-doubt and other concepts, such as self-downing, which revealed that self-doubt acts as a mediator between self-downing and student procrastination.…”
Section: Uses Of the Conceptmentioning
confidence: 99%
“…1,7,25 Regardless of the discipline, few researchers have used and measured the concept of self-doubt. Hardy et al 12 examined the relationship between self-doubt and individuals' intellectual abilities, which provided information on the phenomenon of self-doubt from a personal intellectual competence perspective. Balkis and Duru 13 examined the relationship between self-doubt and other concepts, such as self-downing, which revealed that self-doubt acts as a mediator between self-downing and student procrastination.…”
Section: Uses Of the Conceptmentioning
confidence: 99%
“…Although we have argued that self -discrepancies open oneself up to self -change, it is possible that self-discrepancies leave all of a person’s prime-relevant judgments (e.g., judgments of other people) susceptible to such malleability, and not only those that are related to the self. In a recent article, for example, doubts about one’s own level of academic competence (a potential indicator of self-discrepancies on this dimension) predicted the accessibility of the competence dimension and the degree to which it was used in judging others (Hardy, Govorun, Schneller, Fazio, & Arkin, 2015). We argue that self-discrepancies represent a structural incongruence in the self-representation, and as such, it is the malleability of the active self that should be most predicted by discrepancy magnitude.…”
Section: Studymentioning
confidence: 99%